2009
DOI: 10.1103/physrevb.80.235419
|View full text |Cite
|
Sign up to set email alerts
|

Insulating conduction in Sn/Si(111): Possibility of a Mott insulating ground state and metallization/localization induced by carrier doping

Abstract: The transport properties of the Si͑111͒ ͱ 3 ϫ ͱ 3-Sn surface are investigated by micro-four-point-probe conductivity measurements. The temperature dependence of the surface-state conductivity showed an insulating behavior from room temperature down to 15 K although the surface was believed to be metallic. Furthermore, with changing the band filling by partially replacing Sn atoms with In or Na deposition, we found that the conductivity showed a metallic behavior down to 260 K and upon further cooling, the carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Possible reasons for the gap opening are suggested to be formation of the charge-density waves or Mott-Hubbard insulator ground state. Similar discrepancy between metallic surface band structure revealed by ARPES [12] and nonmetallic electron transport behavior [13], a hard gap singularity at E F by STS at low temperatures [14] was also observed for the Si(111)-…”
Section: Introductionmentioning
confidence: 77%
“…Possible reasons for the gap opening are suggested to be formation of the charge-density waves or Mott-Hubbard insulator ground state. Similar discrepancy between metallic surface band structure revealed by ARPES [12] and nonmetallic electron transport behavior [13], a hard gap singularity at E F by STS at low temperatures [14] was also observed for the Si(111)-…”
Section: Introductionmentioning
confidence: 77%
“…Transport measurements on Sn/Si(111) by a four tip STM have also conclusively shown that resistivity increases when temperature decreases. 17 At variance with the Sn/Ge(111) case, the Sn/Si(111) surface maintains a √ 3 symmetry in the whole temperature range from room temperature to 6 K. Theoretical calculations support that both Sn/Ge(111) and Sn/Si(111) are Mott insulators at low temperature, predicting even magnetism and superconductivity. 18 Magnetic ordering at low temperatures has been recently reported for Sn/Si(111).…”
Section: Introductionmentioning
confidence: 85%
“…Among others, charge density waves (CDW) [e.g., α-Pb/Ge(111)-( √ 3× √ 3) [1,2]] or Mott phases [α-Sn/Si(111)-( √ 3× √ 3) [3]], driven by strong electron-phonon and electron-electron interactions, were discovered for various (sub)monolayer phases. While many of these surface reconstructions come along with metal-insulator transitions, dense monolayers (MLs) of Pb and In on Si(111) reveal superconductivity with critical temperatures below 4 K [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%